Asymmetric total syntheses of callistrilones B, G and J. Issue 9 (22nd March 2018) - Hu, Li-Jun; Cheng, Min-Jing; Cao, Jia-Qing; Zhong, Li-Ping; Hu, Ya-Jian; Wang, Ying; Wang, Lei; Ye, Wen-Cai; Li, Chuang-Chuang
Abstract : A highly concise approach for the first asymmetric and gram-scale total syntheses of callistrilones B, G and J is reported. Abstract : A very concise approach for the first asymmetric and scalable total syntheses of callistrilones B, G and J has been developed. These syntheses proceeded in only 3–4 steps from the commercially available (−)-α-phellandrene (8 ), without the need for protecting groups. The key feature of the syntheses was a biomimetic, diastereo- and regioselective oxidative [3 + 2] cycloaddition.